Boosting the efficiency of organic persistent room-temperature phosphorescence by intramolecular triplet-triplet energy transfer - Weijun Zhao (Nature Portfolio, 2019)
The potential of organic materials with persistent room-temperature phosphorescence for high-tech application is limited by their low efficiency. Here, the authors report a strategy to enhance persistent room-temperature phosphorescence efficiency via intramolecular triplet-triplet energy transfer.